MODIFICAÇOES NA DENSIDADE DE SEMEADURA EM TRIGOS (Triticum Aestivum) DO PADRÃO MULTICOLMO - Battisti, Gabriel K.; Soares, Rômulo D.; Bosa, Diogo; Silva, Adair J. d.; Vezzosi, Leandro F.; Becker, Raquel W.; Crestani, Maraísa; Fernandes, Sandra B. V.; Berto, Jorge; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo